A systematic review examining the characteristics of users of NHS patient medicines helpline services, and the types of enquiries they make. Issue 6 (31st October 2019) - Williams, Matt; Jordan, Abbie; Scott, Jenny; Jones, Matthew
Abstract : Background and objective: Patient medicines helpline services (PMHS) are available from some National Health Service Trusts in the UK to support patients following their discharge from hospital. The aim of this systematic review was to examine the available evidence regarding the characteristics of enquirers and enquiries to PMHS, in order to develop recommendations for service improvement. Methods: Searches were conducted using Medline, Embase, Cumulative Index of Nursing and Allied Health Literature, Scopus, and Web of Science, on 4 June 2019. Forward and backward citation searches were conducted, and grey literature was searched. Studies were included if they reported any characteristics of enquirers who use PMHS, and/or enquiries received. Study quality was assessed using the Axis tool. A narrative synthesis was conducted, and where appropriate, weighted means (WMs) were calculated. Where possible, outcomes were compared with Hospital Episode Statistics (HES) data for England, to establish whether the profile of helpline users may differ to that of hospital patients. Results: Nineteen studies were included (~4362 enquiries). Risk of bias from assessed studies was 71%. Enquirers were predominantly female (WM=53%; HES mean=57%), elderly (WM=69 years; HES mean=53 years) and enquired regarding themselves (WM=72%). Out of inpatient and outpatient enquirers, 50% were inpatients and 50% were outpatients (WM). Six of 15 studies reported adverse effects as the main enquiry reason. Two of four studies reported antimicrobial drugs as the main enquiry drug class. From two studies, the main clinical origin of enquiries were general surgery and cardiology. Across six studies, 27% (WM) of enquiries concerned medicines-related errors. Conclusions: Our findings show that PMHS are often used by elderly patients, which is important since this group may be particularly vulnerable to experiencing medicines-related issues following hospital discharge. Over a quarter of enquiries to PMHS may concern medicines-related errors, suggesting that addressing such errors is an important function of this service. However, our study findings may be limited by a high risk of bias within included studies. Further research could provide a more detailed profile of helpline users (eg, ethnicity, average number of medicines consumed), and we encourage helpline providers to use their enquiry data to conduct local projects to improve hospital services (eg, reducing errors). PROSPERO registration number: CRD42018116276.